Analysis of Economic Growth, Oil Stocks and SIN Stocks in United States - Nurasiah, Iis; Nugraha, Nugraha; Disman, Disman; Yuniarti, Rozmita Dewi; Effendi, Kharisya Ayu (International Journal of Energy Economics and Policy, 2020)
This study aims to examine whether oil stocks can affect US GDP more than sin stocks. Because if oil stocks can increase GDP growth in America, America can reduce the sin stocks that tends to be controversial in society. The data in this study use GDP growth, stock price returns on oil stocks and sin stocks in the United States. Data obtained through the World Bank and reuters in the form of annual data from 2000 to 2017. There are 9 oil companies and 8 sin companies engaged in the alcohol, gambling and tobacco sectors. The data used is time series data. The results of the analysis are that each type of stock has different characteristics. Not all types of stock affect economic growth in a country. In this study, oil stock has no influence on the economic growth of the United States, even though the United States is the largest oil producer in the world. While the sin stocks which is considered an immoral stock actually has a big influence on the economic growth of the United States. Where, the United States also has the largest sin stock in the world. Keywords: economic growth, GDP, oil stock, sin stock JEL Classifications: O13, O47, Q43 DOI: https://doi.org/10.32479/ijeep.9423